Relationships between horizontal jump kinematics and sprint performance in female sprinters and team sport athletes - Johansen, B.; van den Tillaar, R.; Neville, J. (Frontiers in Sports and Active Living, 2025)
The main objective of this study was to investigate how different horizontal jump exercises relate to sprint performance in female athletes, and whether these relationships differ between sprinters and team sport athletes. Twelve female sprinters (age 18.9 ± 3.7 yrs) and twelve team sport athletes (football/handball; age 16.5 ± 2.5 yrs) performed 40 m sprints along with four 30 m horizontal jump tests comprised of: bounding and single leg jumps, each performed for either speed or distance. For single leg jumps, both legs were tested, and the best result was used for analysis. Kinematic variables—horizontal velocity, step length, contact time, flight time, and step frequency—were analyzed across all tasks. A two-way mixed-design ANOVA revealed significant main effects of test type and group, and significant interactions for all variables (p < 0.05). Sprinters showed higher horizontal velocity, longer step length, and shorter contact times across most sprint and jump conditions. Horizontal velocity in the single leg jump for speed showed the strongest correlations with sprint velocity across both groups, with particularly strong associations in sprinters (r = 0.70-0.92). Bounding for speed also correlated strongly with sprint performance in the team sport group (r = 0.57-0.68), but less so in sprinters. Sprint contact time and step length showed variable but often strong associations with corresponding parameters in the jump tests, particularly in the single leg jump for speed. These findings suggest that selected horizontal jump tests may be effective tools for both performance assessment and sprint-specific training.